Non-combative taekwondo evokes highly anaerobic physiological responses in elite-level athletes: potential evidence for a new training modality - Yang, C. Y.; Thurston, T. S.; Cho, E. H.; Cho, J. Y.; Koo, J. H. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Despite the increasing international popularity of taekwondo (TKD) poomsae, there is a lack of physiological characterizations of elite-level competitors in the sport. Thus, the aim of the present study was to investigate the physiological demands associated with various types of TKD poomsae. METHODS: Eight male international TKD poomsae competitors carried out tae-geuk (TG) and professional (PF) poomsaes (in accordance with international competition standards), and consecutive TG (CTG) poomsae (a previously identified poomsae-specific training method). During each poomsae performance, oxygen uptake, heart rate, respiratory exchange ratio, and blood lactate were measured. The physiological responses were normalized and compared to maximal aerobic exercise tests such as a graded treadmill exercise (GXT) and maximal graded arm-crank ergometer exercise (ACE) to analyze the relative exercise intensity of each TKD poomsae. RESULTS: The results showed the relative exercise intensity of TG and PF poomsaes elicit moderate to high intensity physiological proportions of the maximal responses found during the GXT and ACE tests. Interestingly, CTG poomsae responses resulted in similar exercise intensities as those reported during high intensity interval training, indicating that CTG may be an effective training modality to improve aerobic and anaerobic exercise capacity while also utilizing and developing sport specific techniques and skills. CONCLUSIONS: This indicates the need for poomsae athletes to develop and maintain both aerobic and anaerobic capacity to enhance performance. Therefore, these physiological findings will help elite poomsae competitors and coaches to develop exercise programs of substantial duration and intensity to elicit beneficial performance adaptations.